Description of a new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae) - Wang, Ping; Xie, Guanglin; Wang, Wenkai (Zootaxa, 2022)
In this work, a new species of the genus Sinodorcadion Gressitt, 1939 (Cerambycidae: Lamiinae) is described and illustrated, namely Sinodorcadion chizhouensis Wang, Xie & Wang sp. nov. from Anhui, China.